Willingness to start insulin therapy among insulin-naïve persons with type 2 diabetes mellitus at Gulu Regional Referral Hospital, Gulu City, Uganda - Nakitto, Brenda; Opedo, Moses; Nansubuga, Federes; Omondi, Edward; Musinguzi, Emmanuel; Otile, Edwin Cleopas; Ekak, Steven; Nannungi, Christine; Apiyo, Paska; Pebolo, Pebalo Francis; Bongomin, Felix (Therapeutic advances in chronic disease, 2024)
Background: Most patients with type 2 diabetes mellitus (DM2) will require insulin for glycemic control during their disease. Objectives: We evaluated the willingness to start insulin therapy among insulin-naïve persons with DM2 in urban Northern Uganda. Design: A facility-based, quantitative, cross-sectional study was conducted between June and August 2023 recruiting insulin-naïve type 2 diabetes mellitus patients attending routine health care at Gulu Regional Referral Hospital, Gulu, Uganda. Methods: We gauged participants’ willingness to use insulin by asking, ‘If your doctor prescribed insulin for you, would you accept to use it?’ with responses categorized as either ‘Yes’ or ‘No’. Poisson regression analysis was performed to assess the factors associated with willingness to start insulin therapy. p < 0.05 were considered statistically significant. Results: We enrolled 190 participants, with a mean age of 55 ± 12.72 years. Most participants were female (63.7%, n = 121), attained a primary level of education (70.0%, n = 133), and were unemployed (84.2%, n = 160). Overall, 73.4% (n = 138) of the participants were willing to receive insulin therapy if indicated. Participants recently advised on insulin showed a 34% higher willingness [adjusted prevalence ratio (aPR): 1.34, 95% confidence interval (CI): 1.06–1.72, p = 0.007], whereas those with a disease duration of 6 years or more were 43% less willing (aPR: 0.57, 95% CI: 0.39–0.81, p = 0.002) and those concerns about coping with insulin therapy were 55% less willing to commence insulin therapy (aPR: 0.57, 95% CI: 0.39–0.81, p = 0.002). Conclusion: About three in every four participants with DM were willing to receive insulin if indicated. However, healthcare providers should consider personalized counseling strategies to alleviate concerns and enhance informed decision-making regarding insulin initiation. Future interventions should focus on addressing specific barriers associated with prolonged disease duration and apprehensions related to insulin therapy to optimize glycemic control in this population. Plain language summary Exploring readiness for insulin treatment in people with type 2 diabetes at Gulu Regional Referral Hospital, Uganda In this study, we investigated the willingness to start insulin therapy among individuals with type 2 Diabetes Mellitus (DM2) in urban Northern Uganda. Understanding the importance of insulin for glycemic control in DM2, we surveyed 190 participants at Gulu Regional Referral Hospital. We found that more than three-quarters of the participants expressed a willingness to receive insulin therapy if recommended. Factors influencing this willingness included recent advice on insulin, which was associated with a 34% higher likelihood of acceptance. Conversely, individuals with a disease duration of 6 years or more were 43% less willing, and those concerned about coping with insulin therapy were 55% less willing to commence treatment. These findings underscore the need for healthcare providers to offer personalized counseling strategies, addressing specific concerns, to facilitate informed decision-making regarding insulin initiation. Looking ahead, interventions should prioritize overcoming barriers related to prolonged disease duration and apprehensions about insulin therapy to optimize glycemic control and improve the well-being of individuals with DM2 in this population.